Enhancing Leadership Skills: 2024 Training for Muhammadiyah Special Branch (PCIM) in the European and Mediterranean Area - Yordan Gunawan; Faiza Husnayeni Nahar; Sigit Arie Wibowo; Muhammad Annas; Izhan Fakhruzi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The 2024 Leadership Training and Upgrading event for PCIM Leaders and Members in the European and Mediterranean Regions, held in Madrid, Spain, on May 11-12, 2024, marked a significant milestone in Muhammadiyah’s history. Organized by PCIM Spain, this event brought together leaders and members from various countries for the first time, showcasing unprecedented cooperation and unity. The event, themed "Building Quality Diaspora Roles in Promoting Progressive Islamic Da'wah," featured esteemed speakers discussing critical issues such as leadership, security, integration, and social services within the context of Islam and Muhammadiyah. The active involvement and endorsement of the Indonesian Ambassador to Spain, Dr. Muhammad Najib, underscored the strategic importance of this gathering, providing legitimacy and encouragement to the participants. The event also emphasized the crucial role of youth in sustaining and advancing Muhammadiyah's mission, highlighting the need for targeted training, mentorship, and practical leadership experiences. By fostering stronger ties and enhancing cooperation among PCIM branches, the event facilitated the exchange of ideas and best practices, contributing to the realization of Muhammadiyah’s vision of a progressive and inclusive Islamic movement. This pioneering initiative demonstrated the potential of international collaboration in advancing Muhammadiyah's mission and underscored the strategic importance of fostering strong ties among Muslim communities worldwide.